Selective Cu(II) Adsorption from Aqueous Solutions Including Cu(II), Co(II), and Ni(II) by Modified Acrylic Acid Grafted PET Film. (6th August 2013) - Rahman, Nazia; Sato, Nobuhiro; Yoshioka, Satoru; Sugiyama, Masaaki; Okabe, Hirotaka; Hara, Kazuhiro
Abstract : Acrylic acid (AAc) grafted polyethylene terephthalate (PET) films were prepared by γ irradiation. The graft films showed little metal ion adsorption due to compact structure of the graft chains as shown by the scanning electron microscopy (SEM) images which restricted the access of metal ions to the functional groups. Therefore, the graft films were modified with KOH treatment for expansion of the graft chains to facilitate the access of metal ions to the functional groups. The modified films were used to study the selective Cu 2+ adsorption from aqueous solution containing Cu 2+, Co 2+, and Ni 2+ . Langmuir and Freundlich isotherm models were used for interpretation of selective equilibrium adsorption data and Langmuir model showed better fitting with experimental data. Again pseudo-first-order and pseudo-second-order equations were used for interpretation of selective kinetic adsorption data and pseudo-second-order equation showed better prediction of experimental data. The adsorbent film showed high selectivity towards Cu 2+ in presence of Cu 2+, Co 2+, and Ni 2+ in the pH range of 1.5 to 4.5. Desorption and reuse of the adsorbent film were also studied which indicated that the film can be used repeatedly for selective Cu 2+ sorption from aqueous solution.